Heavy metal contamination and health risk evaluation of chestnut ( Castanea sativa Miller) consumed in Turkey - Turhan, Şeref; Turfan, Nezahat; Kurnaz, Aslı (Informa UK Limited, 2022)
This study was performed to determine heavy metals and metalloids in twenty-eight chestnut (Castanea sativa Miller) samples consumed in Turkey by inductively coupled plasma optical emission spectrometry and evaluate health risks for humans through the consumption of chestnut samples. The concentrations of Cd, Cr, Co, Cu, Fe, Pb, Mn, Ni and Zn analyzed in chestnut samples varied from 537 to 635, 608 to 5333, 347 to 972, 207 to 8619, 12,739 to 86,310, 278 to 7549, 8676 to 67,622, 1068 to 18,661 and 3625 to 12,876 µg/kg (dry weight), respectively. The concentrations of Cd and Pb were above the maximum limits determined by the Turkish Food Codex. Healthy risks caused by the heavy metals in the consumed chestnut samples were evaluated by estimating the average daily intake of metal, health risk index (HRI), and total HRI. These results revealed that there is no possible health risk to consumers due to the intake of chestnut samples studied under the current consumption rate.
Keywords: Turkey; Lead; Metals, Heavy; Humans; Risk Assessment; Cadmium; Environmental Monitoring